Game-Based Learning in Improving Interest and Achievement in Physical Education in the 5.0 Era - Louk, Michael Johannes Hadiwijaya; Tajuddin, Al Ihzan; Runesi, Salmon; Fufu, Ronald Dwi Ardian; Neolaka, Erwin Sarnoto; Mae, Ramona Mathias; Wijaya, I Nyoman Wahyu Esa (S&Co Publishing, 2024)
Physical education plays an important role in developing physical health, motor skills, and character building of students. However, the challenge in increasing interest and learning achievement in this subject is still the main focus, especially in the era of education 5.0 which demands an innovative approach. This study aims to explore the role of game-based learning in increasing interest and learning achievement in physical education in the era of 5.0. The research method used is a quasi-experiment with a pre-post test and control group design. The research sample consisted of two classes with 30 students each, one class as an experimental group that received game-based learning, and one class as a control group that received conventional learning. Data were collected through an initial interest test, a learning achievement test, and a questionnaire on students' interest in learning. The results showed a significant increase in the interest and learning achievement of students who participated in game-based learning compared to the control group. Students involved in game-based learning showed higher interest in the subject matter and achieved better learning achievement in terms of motor skills, conceptual understanding, and active participation. In addition, the student interest questionnaire showed that game-based learning provides a more interesting and enjoyable learning experience for students. These findings indicate that game-based learning has great potential in increasing interest and achievement in physical education learning in the 5.0 era.